Prestige or Perish: Publishing Decisions in Academic Archaeology. Issue 4 (October 2021) - Beck, Jess; Gjesfjeld, Erik; Chrisomalis, Stephen
Abstract : Success in academic archaeology is strongly influenced by the publication of peer-reviewed articles. Despite the importance of such articles, minimal research has explicitly examined the factors influencing publishing decisions in archaeology. In order to better understand the landscape of archaeological publishing, we distributed a short survey that solicited basic professional and demographic information before asking respondents to (1) identify journals that publish important archaeological research, (2) identify journals that people who read archaeological academic CVs value most highly, and (3) rank the factors that affected their decisions about where to submit an article for publication. Our results from 274 respondents generated a list of 167 individual journal titles. Prestige was viewed as the most important factor that affected publishing decisions, followed by audience and open access considerations. There was no relationship between respondent-generated journal rankings and SCImago Journal Ranks (SJR), but there were significant differences in average SJR by gender and career stage. Responses showed consensus on only a small number of highly ranked archaeology and science-subject journals, with little agreement on the importance of most other journals. We conclude by highlighting the areas of disciplinary consensus and divergence revealed by the survey and by discussing how implicit prestige hierarchies permeate academic archaeology.